Cardiac Pulsatility– and Respiratory-Induced Deformations of the Renal Arteries and Snorkel Stents After Snorkel Endovascular Aneurysm Sealing. (August 2019) - Cheng, Christopher P.; Suh, Ga-Young; Kim, John J.; Holden, Andrew
Purpose: To quantify deformations of renal arteries and snorkel stents after snorkel endovascular aneurysm sealing (Sn-EVAS) resulting from cardiac pulsatility and respiration and compare these deformations to patients with untreated abdominal aortic aneurysms (AAA) and snorkel endovascular aneurysm repair (Sn-EVAR).Materials and Methods: Ten Sn-EVAS patients (mean age 75±6 years; 8 men) were scanned with cardiac-gated, respiration-resolved computed tomography angiography. From 3-dimensional geometric models, changes in renal artery and stent angulation and curvature due to cardiac pulsatility and respiration were quantified. Respiration-induced motions were compared with those of 16 previously reported untreated AAA patients and 11 Sn-EVAR patients.Results: Renal artery bending at the stent end was greater for respiratory vs cardiac influences (6°±7° vs −1°±2°, p<0.025). Respiration caused a 3-fold greater deformation on the left renal artery as compared with the right side. Maximum curvature change was higher for respiratory vs cardiac influences (0.49±0.29 vs 0.24±0.17 cm −1, p<0.025), and snorkel renal stents experienced similar maximum curvature change due to cardiac pulsatility and respiration (0.14±0.10 vs 0.19±0.09 cm −1, p=0.142). When comparing the 3 patient cohorts for respiratory-induced deformation, there was significant renal branch angulation in untreated AAAs, but not in Sn-EVAR or Sn-EVAS, and there was significant bending at the stent end in Sn-EVAR and Sn-EVAS. Maximum curvature change due to respiration was ~10-fold greater in Sn-EVAR and Sn-EVAS compared to untreated AAAs.Conclusion: The findings suggest that cardiac and respiratory influences may challenge the mechanical durability of snorkel stents of Sn-EVAS; similarly, however, respiration may be the primary culprit for tissue irritation, increasing the risk for stent-end thrombosis, especially in the left renal artery. The bending stiffness of snorkel stents in both the Sn-EVAR and Sn-EVAS cohorts damped renal branch angulation while it intensified bending of the artery distal to the snorkel stent. Understanding these device-to-artery interactions is critical as they may affect mechanical durability of branch stents and quality and durability of treatment.